Mapping the Misconception of Literacy Education among Indonesian Language Teachers: A Certainty of Response Index Analysis - Deby Luriawati Naryatmojo; Apri Pendri; Suhailee Sohnui; Santi Pratiwi Tri Utami (UIN Raden Mas Said Surakarta, Indonesia, 2026)
Indonesia's low literacy achievement in various international assessments indicates that strengthening literacy education remains a significant challenge. At the same time, global literacy concepts have expanded beyond reading and writing to encompass critical, digital, and multimodal competencies. However, in schools where literacy education is often entrusted to Indonesian language teachers, it is still frequently interpreted as merely reading and writing activities, potentially leading to misconceptions. This study aimed to map the levels and types of misconceptions encountered in secondary schools in Central Java, Indonesia. The study employed a mixed-method design in which quantitative data from a Certainty of Response Index (CRI)-based questionnaire and qualitative data from written explanations were integrated during interpretation. The instrument was based on the CRI. The sample included 155 Indonesian language teachers. Data were analyzed using frequency tables and response-type scores. The results showed that misconceptions reached 52.90%, while understanding and not understanding accounted for 34.20% and 12.90%, respectively. The identified misconceptions included (1) implementation patterns, where 66.1% did not differentiate practices across educational levels, 22.4% differentiated them only temporarily, and 11.5% did so routinely; and (2) implementation duration, where 69.9% limited literacy activities to 15 minutes before lessons, while 22.1% implemented them before lessons, during breaks, and throughout learning activities. The integration of CRI scores and participants' explanations indicates that literacy education remains dominated by procedural practices. This study provides empirical mapping of literacy education misconceptions among Indonesian language teachers and highlights the need to redesign literacy education implementation to better support school literacy culture. Rendahnya capaian literasi Indonesia pada berbagai asesmen internasional menunjukkan bahwa penguatan pendidikan literasi masih menjadi tantangan signifikan. Pada saat yang sama, konsep literasi global telah berkembang melampaui kemampuan membaca dan menulis, mencakup kompetensi kritis, digital, dan multimodal. Namun, di sekolah yang cenderung mempercayakan pelaksanaan pendidikan literasi kepada guru Bahasa Indonesia, literasi masih sering dimaknai sebatas aktivitas membaca dan menulis sehingga berpotensi menimbulkan miskonsepsi. Penelitian ini bertujuan memetakan tingkat dan jenis miskonsepsi yang ditemui pada sekolah jenjang menengah di Jawa Tengah, Indonesia. Penelitian menggunakan desain mixed method, dengan integrasi data kuantitatif dari kuesioner berbasis Certainty of Response Index (CRI) dan data kualitatif dari uraian alasan responden pada tahap interpretasi. Instrumen penelitian disusun berdasarkan CRI. Sampel penelitian terdiri atas 155 guru Bahasa Indonesia. Data dianalisis menggunakan tabel frekuensi dan skor tipe respons. Hasil penelitian menunjukkan bahwa tingkat miskonsepsi mencapai 52,90%, sedangkan respons paham dan tidak paham masing-masing mencapai 34,20% dan 12,90%. Miskonsepsi yang teridentifikasi meliputi (1) pola implementasi pendidikan literasi, yaitu 66,1% responden tidak membedakan praktik literasi antarjenjang pendidikan, 22,4% membedakannya secara temporer, dan 11,5% secara rutin; serta (2) durasi implementasi pendidikan literasi, yaitu 69,9% responden membatasi kegiatan literasi pada 15 menit sebelum pembelajaran, sedangkan 22,1% mengimplementasikannya sebelum pembelajaran, saat istirahat, dan selama proses pembelajaran. Integrasi skor CRI dan uraian responden menunjukkan bahwa pendidikan literasi masih didominasi oleh praktik yang bersifat prosedural. Penelitian ini memberikan pemetaan empiris mengenai miskonsepsi pendidikan literasi pada guru Bahasa Indonesia serta menegaskan perlunya redesain implementasi pendidikan literasi agar lebih mendukung penguatan budaya literasi di sekolah.